Free flap transplantation combined with Ilizarov bone transport for the treatment of severe composite tibial and soft tissue defects. Issue 5 (May 2021) - Li, Runguang; Zeng, Canjun; Yuan, Song; Chen, Yirong; Zhao, Shanwen; Ren, Gao-hong
Objective: To evaluate the clinical efficacy of free flap transplantation combined with Ilizarov bone transport in the treatment of severe composite tibial and soft tissue defects. Methods: We retrospectively analyzed the clinical data of 40 patients with severe composite tibial and soft tissue defects who underwent free flap transplantation combined with Ilizarov bone transport. The clinical efficacy was evaluated according to the following criteria: success rate of wound repair by free flap transplantation, incidence or recurrence rate of deep infection, healing rate of bone defects and external fixation index, incidence of complications, and functional score of affected extremities. Results: All infections were generally well controlled by radical debridement and negative-pressure therapy, and all 40 patients' wounds healed after repair and reconstruction of the tibia and soft tissues. Postoperative complications were alleviated by active treatment. The mean external fixation time was 12.83 ± 2.85 months, and the external fixation index was 1.55 m/cm. According to the Association for the Study and Application of Methods of Ilizarov (ASAMI) score, an excellent or good functional outcome was attained in 85% of patients. Conclusion: Free flap transplantation combined with Ilizarov bone transport is an effective treatment for severe composite tibial and soft tissue defects.